THE INFLUENCE OF SERVICE QUALITY ON LOYALTY THROUGH CUSTOMER SATISFACTION AND TRUST AS INTERVENING VARIABLES IN PT. BPR UNIVERSAL KALBAR - Actavianus , Jimmy Renaldo; Purmono, Bintoro Bagus (Lentera Barasaki Publishing House, 2023)
Increased competition is marked by the number of existing banks and product or service competition offered, one of which is PT. BPR Universal West Kalimantan. PT. BPR Universal KalBar is one of the banks that carry out conventional business activities, providing services in payment traffic, borrowing, and withdrawing money. Therefore, for the progress of the company, banks need to pay close attention to consumer demand for a product or service to be offered, one of which is by increasing service quality, trust and customer satisfaction to increase customer loyalty to a banking company located in West Kalimantan, namely PT. BPR Universal KalBar in Pontianak. PT. BPR Universal KalBar tries to satisfy and comfort customers with the services provided. If the customer is satisfied with the service provided, the customer will become loyal. The form of this research is quantitative and causal associative. In this study, the authors used an associative and quantitative causal approach. This study's data collection method used a Likert scale questionnaire. The population in this study are customers of PT. BPR Universal KalBar, which uses a savings product for three months. The sampling technique in this study used a non-probability sampling technique in the form of purposive sampling. A total of 201 samples were used as data in this study. The analytical method used in this study uses the SEM-AMOS approach with the SPSS AMOS 24 application. Based on the results of the research that has been analyzed, it is known that service quality significantly affects customer satisfaction and loyalty. Customer satisfaction also has a significant effect on Trust and Loyalty. Service Quality has a significant effect on Loyalty through Customer Satisfaction. At the same time, Service Quality has no significant effect on Trust. Service Quality has no significant effect on Loyalty through Trust. Customer Satisfaction has no significant effect on Loyalty through Trust.